IMPLEMENTASI KURIKULUM PENDIDIKAN KEWIRAUSAHAAN PADA ANAK USIA DINI DI TAMAN KANAK-KANAK - Early Hari Nugrahini; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the implementation of the entrepreneurship education curriculum for early childhood at TK 'Aisyiyah 18 Kota Madiun. The implemented Merdeka Curriculum emphasizes the development of physical, cognitive, creative, socio-emotional, language, and communication aspects while considering individual differences among children. TK 'Aisyiyah 18 is known for its unique entrepreneurship program, which aims to instill an entrepreneurial spirit from an early age by emulating Prophet Muhammad SAW. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation. The results indicate that the entrepreneurship program at TK 'Aisyiyah 18 successfully instills values of independence, honesty, and self-confidence in children. Supporting factors for the program's success include a conducive school environment, competent educators, and active parental involvement. Challenges in implementation include integrating entrepreneurial values into enjoyable learning themes for children.